Pendekatan Sufistik Dalam Sistem Pendidikan Islam Di Perguruan Tinggi Studi Fenomenologis Program Pencerahan Kalbu di Pesantren Mahasiswa UMI Dar al-Mukhlisin Labbakkang Pangkep - Afifudin Afifudin (INFERENSI: Jurnal Penelitian Sosial Keagamaan, 2017)
The purpose of this study was to to understand the relevance of Sufism with Islamic education and its application as a method and approach of moral-spiritual education Islamic college through Heart Enlightenment Program in Islamic Boarding of UMI Makassar Labbakkang. The method used in this research is qualitative descriptive with phenomenological approach, the methods of collecting the data were observation, interview and study documents. Research findings showed that Islamic education emphasizes on attainment of esoteric quality as a part of human dimension. So that, one of effective methods wich is expected to support the achievement of this aim is sufistic approach. In this case, Sufistic education conducts pedagogical construction through method of takhalli, tahalli and tajalli.